Present State of Land Use and Anthropization in the Poliskyi Region - Samoilenko, V. M.; Bilous, L. F.; Zapototskyi, S. P.; Vishnikina, L. P. (Ukrainian Geographical Journal, 2026)
New model tools for geoinformation analysis of the anthropization of landscapes and physico-geographic taxa are proposed, including a unified categorical-classified scheme, a scale for quantifying such anthropization, and digital choropleths and quasi-spectra of land-use and/or land-cover systems. Using these tools and relevant spatial databases, a cause-and-effect analysis of the current state of land use and anthropization in the Poliskyi region was conducted. The best and worst physico-geographic areas and districts of the region have been identified. The conditionality of regional land-use effects is analyzed by estimating the relationship between areas and geoecologically favorable and unfavorable land-use systems. The results can be applied to regional environmental management schemes and projects to optimize them and implement effective ecological measures while accounting for the war’s environmental impacts.
Keywords: landscapes and physic-geographic taxa; land use; anthropization; quasi-spectra of areas; spatial databases